International Pediatric Otolaryngology Group (IPOG) consensus recommendations: Management of suprastomal collapse in the pediatric population. (December 2020) - Doody, Jaime; Alkhateeb, Ahmed; Balakrishnan, Karthik; Bedwell, Joshua; Carter, John; Choi, Sukgi S.; Cheng, Alan T.; Daniel, Sam J.; Dahl, John; De Alarcon, Alessandro; Fayoux, Pierre; Hart, Catherine K.; et al.
Abstract: Introduction: Suprastomal Collapse (SuStCo) is a common complication of prolonged tracheostomy in children. There is a paucity of literature on this subject, especially regarding how to manage significant suprastomal collapse that prevents safe decannulation. Objective: Provide a definition, classification system, and recommend management options for significant suprastomal collapse in children with tracheostomy. Methods: Members of the International Pediatric Otolaryngology Group (IPOG) who are experts in pediatric airway conditions were surveyed and results were refined using a modified Delphi method. Results: Consensus was defined as > 70% agreement on a subject. The experts achieved consensus: on a standard definition of Suprastomal Collapse that there is clinical importance between significant and insignificant collapse that the gold standard diagnostic modality is endoscopic examination under anesthesia that the severity of collapse is a major determinant in the surgical approach that surgical intervention is the first line management in combined anterior and lateral Suprastomal Collapse. Conclusion: This consensus statement provides recommendations for medical specialists who manage infants and children with tracheostomies with significant Suprastomal Collapse. It provides a classification system to facilitate diagnosis and treatment options for this condition.